Molecular testing of the São Francisco River as an ecological filter for the Brazilian large-eyed stingray Hypanus marianae (Dasyatidae, Myliobatiformes) - Costa, Tiego L. A. (2022)
Ecological niche modeling (ENM) provides information on the potential environmental barriers to a species that can be tested in phylogeographic studies. A previous ENM analysis of the benthic coastal stingray Hypanus marianae revealed a low suitability area for its occurrence at the São Francisco River (SFR) mouth, the fourth largest river flowing into Southwestern Atlantic. Hence, phylogeographic analyses were used to test the hypothesis of two populations: one north and another south of SFR outflow. We sampled 109 specimens in six localities throughout the species’ geographic distribution and sequenced mitochondrial (cytb) and nuclear (rag1) markers. Our analyses corroborated the existence of two groups (ΦST = 0.68, P < 0.0001) within H. marianae, partially agreeing with the ENM results. The commonest mitochondrial haplotype (H2) was shared among almost all localities, except Salvador, where all individuals shared the same and unique haplotype. This group is restricted to a shallow bay area close to SFR, as predicted by the ENM. However, its plume was not effective in isolating a continental island 55 km off the Brazilian coast. While the broad north group is protected in a few Marine Protected Areas, our results suggest that the restricted southern one deserves to be managed specifically.